Effectiveness of Once/Day Dolutegravir Plus Boosted Darunavir as a Switch Strategy in Heavily Treated Patients with Human Immunodeficiency Virus. Issue 4 (22nd March 2019) - Navarro, Jordi; Santos, José Ramón; Silva, Ana; Burgos, Joaquin; Falcó, Vicenç; Ribera, Esteban; Imaz, Arkaitz; Curran, Adrian
Abstract : Study Objective: Dual therapy with once/day dolutegravir (DTG) plus boosted darunavir (DRV/b) may be a suitable and effective strategy with a high genetic barrier to resistance in patients infected with human immunodeficiency virus (HIV). Our aim was to evaluate the effectiveness of DTG plus DRV/b (DTG+DRV/b) as a switch strategy in HIV‐infected patients, irrespective of their history of virologic failure (VF). Design: Multicenter retrospective cohort study. Setting: Human immunodeficiency outpatient treatment clinics at three university hospitals in Spain. Patients: Fifty HIV‐infected adults who had a stable antiretroviral treatment (ART) regimen and an undetectable viral load for at least 6 months, and whose ART was switched to once/day DTG+DRV/b between January 2015 and January 2018 were included in the analysis. Historical genotype at the time of VF was available in 44 patients. Measurements and Main Results: Patients were followed until VF or treatment discontinuation for any reason. The primary outcome was the percentage of patients with a viral load of 50 copies/mL or lower at the last follow‐up visit. Secondary outcomes included changes in CD4 + cell count, lipid profile, and renal function. Of the 50 patients included, median time of viral suppression was 52 months (interquartile range [IQR] 18–103 mo) and nadir CD4 + 89 cells/mm 3 (IQR 37–241 cells/mm 3 ). Patients had a history of a median of 8 ART combinations (IQR 4–11 combinations) and 3 VFs (IQR 2–8 VFs). The historical genotypes from 44 patients showed 41 patients (93.2%) with nucleoside/nucleotide reverse transcriptase inhibitor (NRTI) resistance‐associated mutations (RAMs), 32 (72.7%) with nonnucleoside reverse transcriptase inhibitor (NNRTI) RAMs, and 12 (27.3%) with primary protease inhibitor (PI) RAMs; 7 (15.9%) had darunavir RAMs, and no patients had baseline integrase strand transfer inhibitor RAMs. Thirty‐seven patients (84.1%) had resistance to at least two antiretroviral classes. After a median of 25 months (IQR 17–28 mo) of follow‐up, 49 patients (98%) maintained a viral load of 50 copies/mL or lower, and 1 patient (2%) had VF. No new RAMs emerged at VF. At week 4, serum creatinine concentration increased a median of 0.12 mg/dl (0.03–0.23 mg/dl). At last visit, total cholesterol and low‐density lipoprotein cholesterol levels increased by a median of 9 mg/dl (IQR −18 to 40 mg/dl) and 16 mg/dl (IQR −9 to 40 mg/dl), respectively, whereas CD4 + cell count remained stable (median +13 cell/mm 3 ). Conclusion: In this cohort of heavily treated HIV‐infected patients with virologic suppression, switching to the combination of DTG+DRV/b was a convenient regimen that was highly effective and had good tolerability.